Prospects in straw disintegration for biogas production - Maroušek, Josef (Environmental science and pollution research international, 2013)
The pretreatment methods for enhancing biogas production from oat straw under study include hot maceration, steam explosion, and pressure shockwaves. The micropore area (9, 55, and 64 m(2) g(-1)) inhibitor formations (0, 15, and 0 mL L(-1)) as well as the overall methane yields (67, 179, and 255 CH4 VS t(-1)) were robustly analyzed. It was confirmed that the operating conditions of the steam explosion must be precisely tailored to the substrate. Furthermore, it was beneficial to prepend the hot maceration before the steam explosion and the pressure shockwaves. The second alternative may give increased methane yields (246 in comparison to 273 CH4 VS t(-1)); however, the application of pressure shockwaves still faces limitations for deployment on a commercial scale.
Keywords: Biochemical Phenomena; Methane; Avena; anaerobióza; biopaliva; Explosions; Refuse Disposal; biochemické jevy; High-Energy Shock Waves; Biofuels; Anaerobiosis; methan; odpadky - odstraňování; oves; rázové vlny s vysokou energií; pára; Steam; fermentace; exploze; Fermentation